Benevolent benefactor, beholden beneficiary? Revisiting the promise of self-governance and free association between the Cook Islands and New Zealand. - Ma‘ia‘i, KDee Aimiti (Waka Kuaka, 2025)
Political decolonisation within New Zealand’s Pacific empire resulted in unique and ambiguous “post”-colonial notions of statehood for much of New Zealand’s Realm. This paper considers one such outcome: self-governance and free association (SGFA) in the Cook Islands. It argues that the inability to call on definitive relational bounds—such as former colony and former administrator—has resulted in the formation of an oversimplified caricature. This caricature is dichotomous and is what I have framed as New Zealand as benevolent benefactor and Cook Islands as beholden beneficiary. If New Zealand is taken at its word as a Pacific nation that is sympathetic and culturally attuned to a shared Pacific vision, then the assumption is that it acts as an altruistic member of the Pacific regional order. SGFA becomes evidence of New Zealand’s beneficence, affording the Cook Islands a favourable process of decolonisation at the expense of the New Zealand government. Thus, the argument goes, the Cook Islands benefits more from its association with New Zealand than New Zealand does from its association with the Cook Islands. When this characterisation becomes normalised within political and public consciousness, the way that Cook Islands as a country and Cook Island people as a population are understood is done so through a fragmented and oversimplified stereotype. This paper argues that the benevolent benefactor and beholden beneficiary caricature is not only porous but pernicious; not only has New Zealand gained immeasurable harvest from its associate in the South Pacific, the Cook Islands has not always received the assumed benefits from its continued association.